The Role of Occupational Health and Safety in Mediating the Effects of Job Demands and Job Risks on Employee Performance at PT Pertamina Patra Niaga Surabaya Branch - Akhmad Fatikhul Azzam; Amiartuti Kusmaningtyas; Ida Bagus Cempena (Jurnal Manajemen Bisnis, 2026)
This study employs a quantitative approach utilizing an explanatory causal research design. The population for this study comprises 206 employees at PT Pertamina Patra Niaga Surabaya Branch. The sampling technique utilized was total sampling (saturated sampling), resulting in a final sample size of 206 employees who met the established criteria. Data collection was conducted using google form, with measurement carried out via a likert scale. Subsequently, data processing was performed using the Structural Equation Modeling (SEM) method with the assistance of partial least square (PLS) 4.0 software. The results of this study indicate several key findings: 1) Job demands have a positive and significant effect on occupational health and safety (OHS); 2) Job risk has a positive and significant effect on occupational health and safety; 3) Occupational health and safety has a positive and significant effect on employee performance; 4) Occupational health and safety effectively mediates the relationship between job demands and employee performance; and 5) Occupational health and safety effectively mediates the relationship between job risk and employee performance. Based on these findings, the study recommends that management should proactively assess risks, develop emergency response procedures, and update safety protocols. Additionally, the company must foster a culture of risk reporting that is free from stigma. Furthermore, it is crucial to maintain and increase investment in OHS programs. This should not be done merely for compliance, but as an integral part of the business strategy designed to enhance employee performance, satisfaction, and loyalty.